The Effect of Seaweed (Sargassum sp.) and Plant Extract Combinations on the Growth of Mustard Plant (Brassica juncea L.) Grown in Hydroponic Wick System - Darwin Habinsaran Pangaribuan; Yohannes Cahya Ginting; Rugayah Rugayah; Rosi Oktiya; Echa Dessya Zaheri (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Nutrient solution is an important factor for the growth and quality of hydroponic plants; however, the price is getting more expensive. Seaweed is abundantly available along tropical coast. The study was conducted to determine the best combination of extract of brown seaweed (Sargassum sp.) combined with coconut husk, lamtoro leaves, moringa leaves or African leaves that fit to the nutritional quality of AB mix as hydroponic nutrition for mustard plants. This research was conducted in the greenhouse of the Faculty of Agriculture, Universitas Lampung. The design used was a completely randomized design with six replications. The treatments consisted of six types of treatment, namely AB mix nutrition, brown seaweed, seaweed and lamtoro leaf, seaweed and coconut fiber, seaweed and moringa leaf, seaweed and African leaf. Results showed that the organic nutrient solution extracting from the mixture of brown seaweed with lamtoro leaf or coconut fiber or moringa leaf or African leaf has not been able to fit the quality of AB mix nutrition for mustard plants in the hydroponic wick system. However, among those treatments, the best fresh weight of mustard was found on the treatment of the combination between brown seaweed and lamtoro leaf which was 51.08% from total fresh weight from control AB mix.